Complications of surgically treated pelvic ring injuries with associated genitourinary injuries. Issue 3 (March 2023) - Garay, Mariano; McKinney, Richard; Wheatley, Benjamin; Altman, Daniel T.; Altman, Gregory T.; Westrick, Edward R.
Highlights: Having concomitant pelvic ring injuries and genitourinary injuries resulted in an increase rate of post operative complications. Timing of surgical intervention was not associated with post operative complications. Medical co-morbidities, age, injury severity score, length of stay were not associated with an increased post operative complication rate. Abstract: Objective: Pelvic ring injuries are often associated with vascular and intrapelvic organ injuries including damage to the genitourinary system. The purpose of this study was to examine the relationship between surgically treated pelvic ring injuries and genitourinary injuries. The primary outcome was to determine the rate of post-operative complications including infection, urinary dysfunction, and sexual dysfunction. The secondary outcome was to determine if the time to surgery was associated with post-operative complications. Methods: Retrospective chart review from September 1, 2015 to December 31, 2019 of patients who sustained a pelvic ring injury which required surgical intervention. All patients with closed triradiate cartilage were included. Results: A total of 115 patients met the inclusion criteria, 12 patients with an associated genitourinary (GU) injury were included in the GU group and 103 without GU injury were placed in the non-GU group. The median (range) age of patients in the GU group was 49.5 years (20, 64) and 48 years (15, 92) in the control group ( p  = 0.92). Demographic characteristics including age, Injury Severity Score and Elixhauser comorbidity score were similar between groups. Within the GU group, five patients had an injury to their bladder, four to their urethra and three had an injury to their kidney. In the GU group, one patient developed a wound dehiscence and one developed a urinary tract infection with subsequent sepsis (17%), while in the non-GU group, one patient (1%) developed erectile dysfunction ( p  = 0.028). Regression analysis demonstrated that having concomitant pelvic ring and GU injuries, as well as the number of surgeries were variables associated with post-operative complications, while time to surgery was not. Discussion and conclusions: Pelvic ring injuries with concomitant genitourinary injuries were associated with increased odds of post-operative complications. No differences were noted in complication rates due to the time to surgery between groups.